Forest Before Trees: Letter Stimulus and Sex Modulate Global Precedence in Visual Perception - Álvarez-San Millán, Andrea; Iglesias, Jaime; Gutkin, Anahí; Olivares, Ela I. (Frontiers in Psychology, 2021)
The global precedence effect (GPE), originally referring to processing hierarchical visual stimuli composed of letters, is characterised by both global advantage and global interference. We present herein a study of how this effect is modulated by the variables letter and sex. The Navon task, using the letters 'H' and 'S', was administered to 78 males and 168 females (69 follicular women, 52 luteal women, 47 hormonal contraceptive users). No interaction occurred between the letter and sex variables, but significant main effects arose from each of these. Reaction times (RTs) revealed that the letter ‘H’ was identified more rapidly in the congruent condition both in the global and the local task, and the letter ‘S’ in the incongruent condition for the local task. Also, although RTs showed a GPE in both males and females, males displayed shorter reaction times in both global and local tasks. Furthermore, luteal women showed higher d’ index (discrimination sensitivity) in the congruent condition for the local task than both follicular women and hormonal contraceptive users, as well as longer exploration time of the irrelevant level during the global task than males. We conclude that, according to the linear periodicity law, the GPE is enhanced for compound letters with straight vs. curved strokes, whereas it is stronger in males than in females. Relevantly, luteal phase of the menstrual cycle seems to tilt women to rely on finer grained information, exhibiting an analytical processing style in global/local visual processing.